Answer:
Option ( 2 ) g ( x ) = 2x² + 1
Step-by-step explanation:
[ Refer to the attachment ]
Answer:
x =
Step-by-step explanation:
Given
19 - = 7 ( subtract 19 from both sides )
- = - 12
Multiply both sides by - 4 to clear the fraction and the negative signs
5x + 6 = 48 ( subtract 6 from both sides )
5x = 42 ( divide both sides by 5 )
x =
<span>Simplifying
3x + 6 = 2x
Reorder the terms:
6 + 3x = 2x
Solving
6 + 3x = 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
6 + 3x + -2x = 2x + -2x
Combine like terms: 3x + -2x = 1x
6 + 1x = 2x + -2x
Combine like terms: 2x + -2x = 0
6 + 1x = 0
Add '-6' to each side of the equation.
6 + -6 + 1x = 0 + -6
Combine like terms: 6 + -6 = 0
0 + 1x = 0 + -6
1x = 0 + -6
Combine like terms: 0 + -6 = -6
1x = -6
Divide each side by '1'.
x = -6
Simplifying
x = -6
</span>so the answer is x =-6
According to http://www.geteasysolution.com/3x+6=2x
Answer:
Here you go ! Hope it helps.
Answer:
The answer I got for this equation is x=5
I hope this image helps of showing you how to solve the equation.